Chess as a Powerful Educational Tool for Successful People - Alojzije Jankovic; Ivan Novak (7th International OFEL Conference on Governance, Management and Entrepreneurship: Embracing Diversity in Organisations. April 5th - 6th, 2019, Dubrovnik, Croatia, 2019)
In accordance with the challenges brought out by modern times, it is necessary to adapt to the new circumstances in the field of education. Classical education programs do not provide enough opportunities for individual development, so recently there are many noticeable attempts to refresh existing programs through the introduction of new educational techniques with the aim of better knowledge acquisition in school and preschool age. One of those new techniques is the use of chess, which has proven to be an excellent educational tool through its beneficial factors. Important benefits can be divided into cognitive elements: concentration, memory and logical thinking, as essential skills for the development of each individual; critical thinking factors: improving the ability to assess strengths and weaknesses, establishing value judgments and making decision; and improving creativity through problem solving. Along with these main factors, there are causal-connections with better results in mathematics, improvements in attitude and general behavior, as well as in literacy. What is actually the main advantage of using chess as a formal or informal learning tool in education is that all these benefits can be gained while playing, which is exceptional value in preschool and school age! It is important to emphasize that the chess program also allows to teachers certain freedom for their own creative expression in program implementation in order to raise the attention of children. The aim of this paper is to present in more detail the process of introducing chess as possible education tool in Croatia (and applicable in other countries). Advantages achieved in correlation to the existing programs should be point out, as well as the skills acquired through contact with chess that become one of the most important skills with which individuals can compete in a competitive labor market and in their further life roles, even at the highest management levels.
Keywords: 650; chess; cognitive abilites competitive skills; creativity